Utilización de estrategias metodológicas de pensamiento crítico en el proceso de la lecto-escritura con los estudiantes de quinto grado de educación básica de la Escuela Pacto Andino del recinto ni un paso atrás del cantón Valencia provincia de Los Ríos - Contreras Díaz, Raquel Carolina (2015)
Using methodological strategies of critical thinking in the process of reading and writing to students in the fifth grade of elementary education school Andean Pact enclosure or a step back, contributing to the solution of the problem , similarly to the research development is making a big contribution to basic education. The main objective operationalize the guidelines under the guidance of experts, make the most relevant in the theoretical framework research, it is an integrated, systematic way to perform an activity that must be met in a given time , for which purposes it is proposed to periods considered various alternatives for action ; a form of qualitative research - quantitative , documented field descriptive and feasible project aimed at managers , faculty staff and students of the fifth grade of primary school education in the Andean Pact , project beneficiaries , identified variables for student training School of the Andean Pact , a methodology point parameters in the processing and analysis involve a program of activities with a practical use for the domain of writing in the process of teaching and learning